Pingwei San Ameliorates Spleen Deficiency-Induced Diarrhea through Intestinal Barrier Protection and Gut Microbiota Modulation - Yimeng Fan; Qingyu Zhao; Yuanyuan Wei; Huiru Wang; Yu Ga; Yannan Zhang; Zhihui Hao (MDPI AG, 2023)
Pingwei San (PWS) has been used for more than a thousand years as a traditional Chinese medicine prescription for treating spleen-deficiency diarrhea (SDD). Nevertheless, the exact mechanism by which it exerts its antidiarrheal effects remains unclear. The objective of this investigation was to explore the antidiarrheal efficacy of PWS and its mechanism of action in SDD induced by Rhubarb. To this end, UHPLC-MS/MS was used to identify the chemical composition of PWS, while the body weight, fecal moisture content, and colon pathological alterations were used to evaluate the effects of PWS on the Rhubarb-induced rat model of SDD. Additionally, quantitative polymerase chain reaction (qPCR) and immunohistochemistry were employed to assess the expression of inflammatory factors, aquaporins (AQPs), and tight junction markers in the colon tissues. Furthermore, 16S rRNA was utilized to determine the impact of PWS on the intestinal flora of SDD rats. The findings revealed that PWS increased body weight, reduced fecal water content, and decreased inflammatory cell infiltration in the colon. It also promoted the expression of AQPs and tight junction markers and prevented the loss of colonic cup cells in SDD rats. In addition, PWS significantly increased the abundance of Prevotellaceae, Eubacterium_ruminantium_group, and Tuzzerella, while decreasing the abundance of Ruminococcus and Frisingicoccus in the feces of SDD rats. The LEfSe analysis revealed that Prevotella, Eubacterium_ruminantium_group, and Pantoea were relatively enriched in the PWS group. Overall, the findings of this study indicate that PWS exerted a therapeutic effect on Rhubarb-induced SDD in rats by both protecting the intestinal barrier and modulating the imbalanced intestinal microbiota.